21 Years Activity of the ITAU Activities. Issue Volume 15:Issue S367(2019) (December 2019) - Baghbani, Hasan; Rokni, Mahdi; Tomita, Akihiko; Hadizadeh, Maryam
Abstract: ITAU, the Iranian teacher's astronomy union, has attempted for many years to introduce astronomy to the teachers and students not only in Iran but also around the world by providing various materials and projects. The primary goal of ITAU is also to protect the environment with a help of students; therefore, first, try to change the attitude of students. SINA, Student's International Network for Astronomy, will follow the goals.